Upaya Peningkatan Hasil Belajar Fiqih dengan Menggunakan Metode Picture and Picture pada Siswa Kelas V MIN 20 Bireuen - Fadhla, Anna (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
Student learning outcomes during the learning process are strongly influenced by the methods applied by the teacher in teaching. The use of appropriate methods in teaching must be in accordance with the surrounding environment, so that the methods applied can function properly. The purpose of the research is to explain the learning outcomes of class V MIN 20 Bireuen on Hajj material using the picture and picture method, to describe the activities of teachers and students in improving learning outcomes of Jurisprudence on Hajj material using the picture and picture method and to explain student responses during the learning process Jurisprudence on Hajj material using the picture and picture method. This type of research is qualitative with a Classroom Action Research (CAR) approach. The research subjects were 18 students of class V MIN 20 Bireuen. Data collection techniques with observation, interviews, test questions, and documentation. Presentation of material using pictures related to Hajj material and providing evaluation before closing learning activities. The results showed that the effort to improve learning outcomes of Jurisprudence on Hajj material by using the picture and picture method for students of class V MIN 20 Bireuen, has increased, from the previous students who completed learning only 16.66%, after using the picture and picture method in cycle I the number of students who completed reached 55.55%. In cycle II there was an increase in the number of students who completed 94.44%. It was concluded that learning Fiqh on Hajj material using the picture and picture method can improve student learning outcomes.